THE MANAGEMENT OF AGRICULTURAL TOURISM WITH THE POSDCoRB CONCEPT - Praditsangthong, Pattamet; Submahachok, Patsornkun; Seisawatwanit, Patyamon (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2022)
Agro tourism, it is an eco-tourism. The owner of the orchards provides tourists into fruit orchards, they have an accommodation, activities and entertainment is offered to the customer. Agro tourism makes visitors interested in the taste of rural life and culture through recreation and learning such as gardening, plant care, branching, environmental learning, fertilizer use, soil remediation, insecticide disposal and agricultural products distribution. This helps to increase revenue and create local jobs. It gives new opportunities for agricultural interested in rural areas. Sustainable agrotourism, operators will need to implement Gulick’s POSDCoRB management philosophy to effectively manage their gardens. The principle of division is to do the job by aptitude or by dividing the work into the objective process and the internal unit by function or activity. There is a clear mandatory line. The budgetary framework is controlled. Finally, monitoring and evaluation the implementation in order to achieve the goal and the achievement of the objectives.